The use of short stories for personal response at SMK Sematan: a case study / Tracey Levira Anak John Jatot - John Jatot, Tracey Levira (2011)
Personal response in English has never been easy for students especially those from the rural areas. Even though in Malaysia English is the country’s second language, due to the country’s diverse background, English is perhaps the third or the fourth language spoken after the ‘mother tongue’, the standard Malay language and the other languages (if any) spoken by some Malaysians. English is perhaps a foreign language to some Malaysians. In SMK Sematan, students who mostly come from the Malay, Chinese and Bidayuh background normally put their mother tongue first in interaction, followed by Sarawak Malay, the Standard Malay, and then English. Hence, with this limited exposure in English, getting the students to give personal response in the language is a daunting task. Since the introduction of literature in the English language syllabus, one of its main aims is to get students to respond to the text personally. Therefore in this study, a research was done on the use of the two short stories ‘QWERTYUIOP’ and ‘The Fruitcake Special’ learnt by the upper form students to determine its effectiveness in promoting personal response. Ninety form four students and five teachers were selected as the sample for this study and the methods used to determine the results are testing and questionnaire. The result of the study is then generated from SPSS using the Descriptive Statistic Analysis method focussing on frequency, percentage and mean. In this study, the result shows that personal response through the two short stories is not quite effective due to students’ poor language. Teachers’ approaches and choice of activities contribute to students’ poor language. Therefore, teachers’ are encouraged to take some steps to improve their approaches and activities in the classroom to help students to improve their language first before promoting personal response.